Properties of Carbon Dioxide Foam Stabilized by Hydrophilic Nanoparticles and Hexadecyl Trimethyl Ammonium Bromide - Li, Songyan; Qiao, Chenyu; Wanambwa, Silagi (Energy & Fuels, 2017)
Nanoparticles can improve the stability of CO2 foam and increase oil recovery during CO2 flooding in reservoirs. The synergistic effect of hydrophilic SiO2 nanoparticles and hexadecyltrimethylammonium bromide (CTAB) on CO2 foam stability was examined in this study. Experimental results show that the synergistic effect requires a CTAB/SiO2 concentration ratio of 0.02–0.07, with 0.033 representing the best concentration ratio. With the increase in the concentration ratio, the synergistic stabilization effect of CTAB/SiO2 dispersion first increases and then decreases. In the monolayer adsorption stage (concentration ratio from 0.02 to 0.033), when the hydrophobicity of SiO2 nanoparticles increases with the concentration ratio, the nanoparticles tend to adsorb on the gas–liquid interface and the stability of CO2 foam increases. In the double-layer adsorption stage (concentration from 0.033 to 0.07), when the hydrophobicity of SiO2 nanoparticles decreases with an increase in the concentration ratio, the nanoparticles tend to exist in the bulk phase and the stability of CO2 foam decreases. The CTAB/SiO2 dispersion stabilizes CO2 foam via three mechanisms: decreasing the coarsening of CO2 bubbles, improving interfacial properties, and reducing liquid discharge. CTAB/SiO2 foam can greatly improve oil recovery efficiency compared to water flooding. Experimental results provide theoretical support for improving CO2 foam flooding under reservoir conditions.
Keywords: hydrophilic nanoparticles, synergistic effect, CO2 foam, stabilization, oil recovery